First Vacuum-Assisted Excision of a Breast Myofibroblastoma - B. Fakim; A. Abbas; M. Crotch-Harvey; J. Kokan (Case Reports in Surgery)
A 52-year-old lady was seen in the breast clinic after an 8 mm lesion was found in her left breast on screening mammogram. Clinical examination was normal. The left breast mammogram showed an 8 mm rounded density posteriorly in the inner half of breast and ultrasound also showed a 7 mm, well-defined ovoid echogenic lesion (R3, U3). Biopsy confirmed the lesion was fibro-fatty tissue containing a diffuse infiltrate of lymphoid cells macroscopically (B3/4)—findings in line with a diagnosis of a myofibroblastoma. A myofibroblastoma is a rare benign mesenchymal tumour comprising of spindle cells. Most breast myofibroblastomas described in the literature have been excised by wide local excision. In this patient’s case, a vacuum-assisted technique was discussed and suggested at the multidisciplinary meeting. It was excised using ultrasound-guided Vacora® breast biopsy system. The lesion was completely excised with the encore biopsy measuring 24×17 mm. This is the first documented case of such a technique for the excision of a breast myofibroblastoma. There still is uncertainty about breast myofibroblastomas, their aetiology, associations, and how they are best investigated. Regarding management, vacuum-assisted technique, being less invasive and cheaper than local excisions, is adequate for small lesions.